Kearsipan Sebagai Upaya Peningkatan Kualitas Pembelajaran di SD Muhammadiyah Karangploso - Martono Martono; Rahardiyono Rahardiyono; Yugara Pamekas (Journal on Education, 2023)
Improving the quality of learning in schools is determined by several factors, namely facilities and infrastructure, environment, competence of school principals and teachers, administrative staff, librarians, and a conducive climate in schools. One factor that has received less attention is the competence of the school component in managing school archives. In this regard, archive management skills training is seen as a good strategy to improve the quality of learning. This training aims for all school components to have the same vision and skills in viewing the importance of managing archives. This research was conducted for 5 months with the target of all components of SD Muhammadiyah Karangploso school. The aspects that are the focus of this research are the training process, and the practice of managing records in schools and their learning practices. Instruments used include questionnaires, interview guidelines, observation, and documentation. The results of this study are expected to benefit all components of the school, especially SD Muhammadiyah Karangploso.